The Elimination of Person’s Badness After Converting to Islam: The Science of Hadith and Hadith Al-Ahkam Perspective - Nuryamin, Nuryamin; Masâ€™ud, Muhammad; Haidan, Haidan; Supala, Supala; Farid, Diana (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2019)
This article reports on the results of á¸¥adÄ«th research on the elimination of a person's badness after someone converts to Islam. The narration (riwÄyat) of á¸¥adÄ«th is found in á¹¢aá¸¥Ä«á¸¥ al-BukhÄrÄ«, KitÄb al-ÄªmÄn, BÄb á¸¤usn IslÄm al-Marâ€™. This study uses the takhrÄ«j al-á¸¥adÄ«th method. The findings of this study reveal that the narration of the á¸¥adÄ«th is classified muâ€™allaq (suspended). Without considering the statements or explanations from the commentators of á¹¢aá¸¥Ä«á¸¥ al-BukhÄrÄ«, this study concludes that the narration of the á¸¥adÄ«th is categorized á¸aâ€™Ä«f (weak), because the sanad (chain of narrators) was munqaá¹iâ€™ (interrupted). However, after searching another sanad, it found other narrations of á¸¥adÄ«th continued to the Prophet, so that the sanad is muttaá¹£il (connected). In other words, the status of the sanad of á¸¥adÄ«thin á¹¢aá¸¥Ä«á¸¥ al-BukhÄrÄ« was changed from munqaá¹iâ€™ (broken) to muttaá¹£il (connected) and was judged á¹£aá¸¥Ä«á¸¥ (sound) by the scholars, except Ibn á¸¤azm. Because of the soundness, the narrations of á¸¥adÃ®thare also found in the works of other scholars, such as á¸¥adÃ®th al-aá¸¥kÃ¢mand fiqh.